2023
DOI: 10.1093/braincomms/fcae017
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome deficiency results in age-dependent development of epilepsy

Hanna Leister,
Felix F Krause,
Beatriz Gil
et al.

Abstract: The immunoproteasome is a central protease complex required for optimal antigen presentation. Immunoproteasome activity is also associated with facilitating degradation of misfolded and oxidized proteins, which prevents cellular stress. While extensively studied during diseases with increasing evidence suggesting a role for the immunoproteasome during pathological conditions including neurodegenerative diseases, this enzyme complex is believed to be mainly not expressed in the healthy brain. Here, we show an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…As indicated above, aging, and more specifically senescence is marked by an altered redox state, an accumulation of oxidized proteins, and, as a consequence, by an increase of the immuno-proteasome activity. In 2018, we demonstrated for the first time that piperlongumine and some of its analogues can act in vitro as selective inhibitors of the immuno-proteasome . Importantly, and as previously suggested by Jarvius et al, we showed that this inhibition, which occurs at an IC 50 of 15.0 μM, does not affect the constitutive proteasome .…”
Section: Introductionsupporting
confidence: 80%
“…As indicated above, aging, and more specifically senescence is marked by an altered redox state, an accumulation of oxidized proteins, and, as a consequence, by an increase of the immuno-proteasome activity. In 2018, we demonstrated for the first time that piperlongumine and some of its analogues can act in vitro as selective inhibitors of the immuno-proteasome . Importantly, and as previously suggested by Jarvius et al, we showed that this inhibition, which occurs at an IC 50 of 15.0 μM, does not affect the constitutive proteasome .…”
Section: Introductionsupporting
confidence: 80%